Morphometrical studies on the developing adrenal gland in crossbred goats (Capra hircus)* - Ashok, N; Harshan, K R; Chunghat, J J (The Indian Journal of Animal Sciences, 2005)
A morphometrical study was conducted on 17 sexually indifferent and 38 male goat foetuses. The adrenals attained a harvestable size around 59 days of gestation. The adrenal weight, length. breadth and thickness increased from 59 days to full term with a spurt in the combined adrenal weight after 141 days of gestation. Though the absolute adrenal weight increased during gestation, the adrenal to body weight percentage did not increase significantly. The left adrenal was slightly heavier thal the right.